Pendampingan Pemanfaatan Botol Plastik Bekas sebagai Media Tanam Ramah Lingkungan - Bariroh, Muflihatul; Nisa, Nadia Qoirun; Wulandari, Vita; Arido, Yusif Fais; Aziz, Wafa Abdul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service article discusses the program Utilization of Used Plastic Bottles as Environmentally Friendly Planting Media at SDN 1 Besuki, Tulungagung, conducted on July 14, 2025, involving 45 students. The activity was initiated in response to the increasing volume of non-biodegradable household plastic waste, aiming to enhance environmental literacy, recycling skills, and pro-environmental attitudes through participatory learning. The method integrated Participatory Action Research (PAR) and Asset-Based Community Development (ABCD), positioning students as active participants and leveraging local assets. The program stages included providing education on the environmental impacts of plastic waste, designing activities, collecting materials, conducting technical demonstrations, hands-on pot-making practice, and evaluation through participatory observation. The results indicated improved students’ understanding of the ecological risks of plastic and their skills in transforming bottles into functional and aesthetic pots. Enthusiasm was evident from active participation in discussions and practical sessions. The main challenges encountered were limited equipment, short duration, and difficulties in installing hanging wire supports. Nevertheless, the outputs met the learning objectives and have the potential to be developed into routine activities or environmentally friendly entrepreneurship initiatives. Recommendations include extending the training duration, providing additional equipment, strengthening mentoring, and integrating the program into local content curricula.